INTERNATIONAL TERRORISM AND CENTRAL ASIA: PREMATURE ASSESSMENTS - SABOL, Steven (CENTRAL ASIA AND THE CAUCASUS, 2008)
In the months leading up to, and the first few years after, the Soviet Union collapsed numerous articles and books were published that claimed Islamic “fundamentalism” was likely to emerge in Central Asia. These fears were predicated on numerous scenarios, the most important being the ongoing political and military crisis in Afghanistan and Iranian attempts to increase its influence in the region. I will argue, however, that these concerns were premature and that the real threat to the stability and security of Central Asia, and the potential threat of Islamic radicalism, is more likely to be during the next transitional phase when the current repressive regimes are replaced by new leaders,what I refer to as the “post-transition transition.”1 I do not believe that Islamists and their actions are the threat, rather that the rhetoric coupled with actions will be used to discredit subsequent leaders and that internal, factional political rivalries will embrace whatever means necessary to eliminate opposition. In this scenario, the power of Islamic rhetoric and propaganda will influence and alter the political evolution in Central Asia and its devolution from authoritarian structures toward liberal democracies. Therefore, the purpose of this paper is to posit an argument that early assessments were “pre-mature” and rather alarmist based upon real and perceived weaknesses in Central Asia rather than a better comprehension of the strength and vitality exercised by the transitional regimes. At the conclusion, I have four (although more can be posed) questions designed to augment our “assessments” of the current social, economic, and political transition that is occurring in the region.